Bread revolution : world-class baking with sprouted and whole grains, heirloom flours, and fresh techniques - Reinhart, Peter (Ten Speed Press, 2014)
"An exploration of cutting-edge developments in the bread baking world from beloved author Peter Reinhart, featuring 40 recipes and formulas that use sprouted flours, whole and ancient grains, alternative grains (such as corn and grape skin flour), nut and seed flours, and allergy-friendly approaches. Renowned baking author and instructor Peter Reinhart has always been on the forefront of the bread movement--from cold fermentation (The Bread Baker's Apprentice) and whole grain breads (Peter Reinhart's Whole Grain Breads) to unconventional methods for making gluten-free bread (The Joy of Gluten-Free, Sugar-Free Baking). In Bread Revolution, he explores the latest groundbreaking new flours based on grape seeds, emmer, and other ancient grains, and interviews intrepid bakers such as Craig Ponsford, Keith Giusto, and Mike Pappas, who are developing new wheat processing and baking techniques that expose tremendous flavor and health benefits. This on-trend collection of fresh bread recipes will appeal to avid bakers, health-conscious cooks, and food allergic, gluten-sensitive, and diabetic households"--